Game-board of the round game "Strikes" played by the family Marx. The game-cover: BG B3/16. Original in Marx/Engels archive E 92 (E 45)
Game-board of the round game "Strikes" played by the family Marx. The game-cover: BG B3/16. Original in Marx/Engels archive E 92 (E 45).